0.4 millimeters vertically aligned carbon nanotubes from a cold wall CVD system at low pressure – Temperature analysis. (April 2022) - Machado Jr., George
Abstract: This paper reports a temperature study on the new method recently proposed by the author to grow tall vertically-aligned carbon nanotubes (VA-CNT) in a cold-wall system, using a two-phase deposition step at low pressure. The first test consists of run several growths varying the annealing and deposition temperature. Secondly, a third phase, with H2 and higher temperature (850 °C), is added to the deposition step, including a purge between the three phases to recondition the chamber reactor. The goal here is to verify if the chamber reconditioning and an extra phase at higher temperature contributes to increase the height and the uniformity of the VA-CNT forests. After this test, a new test for the annealing temperature is performed to find the sweet spot (temperature for each the highest and uniform forest are obtained). The first test demonstrated that the VA-CNT forests are higher as the annealing temperature decreases. Moreover, the best results were obtained when the annealing temperature is inferior to the growth temperature. Adding a third phase with H2 to the deposition step resulted in an increase in average height of the forests from 186 µm to 272 µm, an increase of almost 100 µm. Finally, adjusting the annealing temperature confirmed that the best results are found for lower values of temperature. The best average height, 404 µm, with a standard deviation of 16.3 µm, was achieved with a three-phase deposition step and an annealing temperature of 600 °C.